2015
DOI: 10.1016/j.jbiomech.2015.04.028
|View full text |Cite
|
Sign up to set email alerts
|

In vivo recruitment patterns in the anterior oblique and dorsoradial ligaments of the first carpometacarpal joint

Abstract: The anterior oblique ligament (AOL) and the dorsoradial ligament (DRL) are both regarded as mechanical stabilizers of the thumb carpometacarpal (CMC) joint, which in older women is often affected by osteoarthritis. Inferences on the potential relationship of these ligaments to joint pathomechanics are based on clinical experience and studies of cadaveric tissue, but their function has been studied sparsely in vivo. The purpose of this study was to gain insight into the functions of the AOL and DRL using in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…As described, but not quantified, by Edmunds: “During the screw‐home torque phase of opposition, the anterior oblique ligament is completely lax and thus plays no role in prevention of dorsal subluxation, while there is a tensioning of the dorsal ligament complex, coupled to muscles action in the last phase of opposition, which drives the volar beak of the MC1 into its recess in the trapezium for rigid stability”. The important stabilizing function of the dorsal ligaments is also supported by recent studies …”
Section: Discussionsupporting
confidence: 52%
“…As described, but not quantified, by Edmunds: “During the screw‐home torque phase of opposition, the anterior oblique ligament is completely lax and thus plays no role in prevention of dorsal subluxation, while there is a tensioning of the dorsal ligament complex, coupled to muscles action in the last phase of opposition, which drives the volar beak of the MC1 into its recess in the trapezium for rigid stability”. The important stabilizing function of the dorsal ligaments is also supported by recent studies …”
Section: Discussionsupporting
confidence: 52%
“…The assumption underlying this method was that the final static orientation and position of the metacarpal is a result of the combined muscle, joint contact, and ligament forces. However, ligament contribution to this force is thought to be minimal, as prior studies show TMC ligaments to be lax during the ranges of motion studied [28]. Since the TMC cartilage was not visible in the CT images, we represented cartilage as a uniform thickness of 0.7 mm with neo-hookean properties.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant force vector of all external forces onto the joint was passed through the centroid of the first metacarpal towards the trapezium to bring the two cartilage surfaces into contact. We assumed no contribution from ligaments during these postures [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, both the DRL and SAOL lengthened during adduction of the first CMC joint and both the POL and dAOL lengthened during abduction of the joint. Halilaj et al 5 also evaluated the changes in the lengths of the DRL and AOL during the first CMC motions using in vivo kinematics data. They indicated that the AOL was slack in most of the range of CMC joint motion, whereas the DRL was in tension in positions that involve joint flexion and adduction, similar to our findings.…”
Section: -12mentioning
confidence: 99%
“…1 Therefore, the first CMC ligaments are thought to play an important role in the maintenance and stability of the first CMC joint. [2][3][4][5][6][7][8][9][10][11][12] Currently, several studies on the anatomy of the first CMC ligaments have been reported in cadaveric dissections. 2,6,[8][9][10][13][14][15] Presently, Bettinger et al 2 and Nanno et al 8 have described seven ligaments in examining the complex ligamentous anatomy of both the first metacarpal and the trapezium.…”
Section: Introductionmentioning
confidence: 99%